A Rapid Special Staining Technique for Identification of Normal Ureter by Frozen Section in Children With Ureteropelvic Junction Obstruction. (December 2019) - Babu, Ramesh; Vittalraj, Pavithra; Sundaram, Sandhya; Pothankulankara Manjusha, Mullappali; Ramanan, Venkat; Sai, Venkata
Background: The exact etiology of ureteropelvic junction obstruction (UPJO) is unknown, and inadequate excision of the narrow segment has been proposed as a cause of failure in 5% to 7% of cases of pyeloplasty. Aims: To study whether frozen section can be useful to detect normal ureter distal to UPJO during pyeloplasty. Methods: Histological sections from 31 patients with UPJO were analyzed for collagen to muscle ratio (CMR) on conventional (formalin) and rapid (frozen section) Masson's trichrome staining. Pathological findings were correlated with postoperative outcomes analyzed at 1-year follow-up and expressed as excellent, moderate, or mild improvement, static and deterioration based on ultrasound grade, differential renal function, and renogram drainage pattern. Results: There was a very strong positive correlation ( r = .94; P = .001) between CMR by conventional and rapid frozen Masson's trichrome staining. There was a very strong negative correlation between pyeloplasty outcomes and CMR on conventional staining ( r = −.94; P = .001) or rapid frozen Masson's trichrome staining ( r = −.91; P = .001). Regression analysis revealed that a CMR of 1.2 or less (95% confidence interval: 1.9–0.7) was associated with a successful outcome. Conclusions: It is feasible to intraoperatively identify normal ureter distal to UPJO using CMR analysis on the novel rapid frozen section technique reported.